Augmentation of potential phosphate solubilizing bacteria (PSB) stimulate growth of green mustard (Brasica caventis Oed.) in marginal soil - SRI WIDAWATI; SULIASIH SULIASIH (Society for Indonesian Biodiversity, 2006)
The potential of phosphate solubilizing bacteria/PSB (Bacillus megaterium, B. pantothenticus, Chromobacterium lividum and Klebsiella aerogenes) were used as biofertilizer to increase the fresh leaf production of green mustard (Brasica caventis Oed.). An experiment was conducted at green house condition. The experiment were used 18 treatments such as single isolate of potential PSB (A,B,C,D), inoculants contain two isolates of potential PSB (E,F,G,H,I,J), inoculants contain three isolates of potential PSB (K, L, M, N), inoculants contain four isolate of potential PSB (O), chemistry fertilizer (P = control 1), organic fertilizer (Q = control 2), and without fertilizer (R = control 3). The treatments were arranged in Completely Randomized Design (CRD) with 5 replications. The result showed that the inoculants of potential PSB increased the fresh plant production of green mustard. The mix of four isolates of potential PSB (inoculants O) was the best to increase the fresh plant production of green mustard until 32.87% than other PSB inoculants, 207.84% than control 1,217.23% than control 2, and 930.60% than control 3. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: BPF/PSB, Wamena Biological Garden, Brasica caventis Oed.